Aversion caused by skin diseases – a crowdsourcing study - Pereira, Priscilla A. [UNESP]; Miot, Helio A. [UNESP]; Coutinho, Thales V.; Schmitt, Juliano Vilaverde [UNESP] (Wiley, 2018)
Background: Disgust is a universal emotion that plays a role in reducing people's exposure to situations with risks of contamination. By the same token, skin diseases could generate aversion in observers. The present study aimed to assess the aversion triggered when viewing skin disease lesions on the face and hands. Methods: A questionnaire was applied over the Internet containing demographic questions, assessment of personal sensitivity to disgust – by the Disgust Scale-Revised (DS-R) -, and the aversion triggered when viewing eight images of skin diseases using an image aversion score (IAS) ranging from 0 to 10. Results: Six-hundred forty-nine people responded, 49% female, with a median age of 26 (p25–p75: 22–34). A total of 2596 evaluations of images were collected. The overall IAS median was 2 (0–4), and Cronbach's alpha resulted 0.87. There was a significant correlation between DS-R and IAS (Spearman's rho = 0.42; P < 0.01). Seven-hundred twenty-four (28%) evaluations were considered as contagious diseases and received higher IAS: 5 (2–7) × 1 (0–3); P < 0.01. In multivariate analysis, the higher IAS was independently associated with male gender, with no children, not working as a health professional or caregiver, and presenting higher DS-R (P < 0.01). By analyzing the IAS according to morphological characteristics, we identified lower scores for macular dyschromic lesions (P < 0.01). Conclusions: The aversion triggered by skin lesions varies according to the personal characteristics of the observer and the morphology of the lesion, being lower for macular dyschromic lesions, and associated with disgust sensitivity and the assignment of contagiousness to the lesion.